Open versus Laparoscopic Appendectomy: A Literature Review - Nicole Kiril Nikolov; Hannah Theresa Reimer; Alvin Sun; Benjamin David Bunnell; Zachary Isaac Merhavy (Journal of Mind and Medical Sciences)
Appendectomy is the most common emergency abdominal surgery in the United States. Open appendectomy has been the standard procedure for decades, whereas laparoscopic appendectomy is a newer, less-invasive method of removing the appendix. This review intends to elucidate the similarities and differences between these two procedures as well as explore the advantages and disadvantages of each approach. Socioeconomic factors, associated costs, preoperative imaging, operative time and methods, length of hospital stay, recovery time, and complications associated with open and laparoscopic appendectomy are discussed. Overall, laparoscopic appendectomy has shorter hospital stays and recovery times, requires less analgesics, and results in better postoperative outcomes. Although such an analysis/comparison involves several perspectives, a review of the available literature suggests that laparoscopic appendectomy is the operation of choice in most cases.